Nitrogen Sinks or Sources? Denitrification and Nitrogen Removal Potential in Riparian Legacy Sediment Terraces Affected by Milldams. Issue 10 (29th September 2022) - Peck, Erin. K.; Inamdar, Shreeram; Sherman, Melissa; Hripto, Johanna; Peipoch, Marc; Gold, Arthur J.; Addy, Kelly
Abstract: Riparian zones are key ecotones that buffer aquatic ecosystems through removal of nitrogen (N) via processes such as denitrification. However, how dams alter riparian N cycling and buffering capacity is poorly understood. Here, we hypothesized that elevated groundwater and anoxia due to the backup of stream water above milldams may enhance denitrification. We assessed denitrification rates (using denitrification enzyme assays) and potential controlling factors in riparian sediments at various depths upstream and downstream of two relict U.S. mid‐Atlantic milldams. Denitrification was not significantly different between upstream and downstream, although was greater per river km upstream considering deeper and wider geometries. Further, denitrification typically occurred in hydrologically variable shallow sediments where nitrate‐N and organic matter were most concentrated. At depths below 1 m, both denitrification and nitrate‐N decreased while ammonium‐N concentrations substantially increased, indicating suppression of ammonium consumption or dissimilatory nitrate reduction to ammonium. These results suggest that denitrification occurs where dynamic groundwater levels result in higher rates of nitrification and mineralization, while another N process that produces ammonium‐N competes with denitrification for limited nitrate‐N at deeper, more stagnant/poorly mixed depths. Ultimately, while it is unclear whether relict milldams are sources of N, limited denitrification rates indicate that they are not always effective sinks; thus, milldam removal—especially accompanied by removal of ammonium‐N rich legacy sediments—may improve riparian N buffering. Plain Language Summary: Floodplains adjacent to rivers are important ecosystems that provide valuable services including nutrient removal, especially nitrogen, from stream water. Because nitrogen is a major polluter of coastal waters, river floodplains are increasingly being restored as part of watershed best management practices. For example, millions of dollars are being spent annually in the Chesapeake Bay to install 900 miles of riparian buffers and on other watershed practices to mitigate nutrient pollution. However, the impact of small, colonial‐era milldams on floodplain nitrogen mitigation is poorly understood, despite >14, 000 such structures still present across streams of the eastern United States. We studied the impact of two small milldams (Roller mill on Chiques Creek, Lancaster, Pennsylvania, and Cooch mill on Christiana River, Newark, Delaware) on the ability of floodplains to remove or store nitrogen. We found that the stagnant water that accumulates behind milldams restricts floodplains from effectively removing nitrogen and may actually cause the accumulation of nitrogen. Whether accumulated nitrogen is released back into streams is unknown but concerning. Removal of dams would likely improve many ecosystem services of both streams and floodplains, with minimal consequences for the nitrogen mitigation abilities of these ecosystems. Key Points: Riparian denitrification rates are similar above and below milldams but deeper, wider upstream zones result in more nitrogen removal Denitrification rates peak in shallow sediments of riparian areas above milldams with higher hydrologic variability Stagnant hydrologic conditions upstream of milldams promote nitrogen processes that result in ammonium accumulation at deep sediment depths